2016
DOI: 10.1038/srep37069
|View full text |Cite
|
Sign up to set email alerts
|

Deep Breathing Practice Facilitates Retention of Newly Learned Motor Skills

Abstract: Paced deep breathing practices, a core component of a number of meditation programs, have been shown to enhance a variety of cognitive functions. However, their effects on complex processes such as memory, and in particular, formation and retention of motor memories, remain unknown. Here we show that a 30-minute session of deep, alternate-nostril breathing remarkably enhances retention of a newly learned motor skill. Healthy humans learned to accurately trace a given path within a fixed time duration. Followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
(55 reference statements)
0
33
1
Order By: Relevance
“…Deep breathing practices, which generally involve inhalation and exhalation of air at a slow rate that is different from regular breath cycles, form an integral component of many meditation programs (Brown and Gerbarg, 2009). A number of studies show that the deep breathing practice may result in marked beneficial effects across a variety of cognitive functions, including inhibitory control, working memory, and attention and emotion regulation (Busch et al, 2012; Brown et al, 2013; Vlemincx et al, 2016; Yadav and Mutha, 2016). Depending on the breathing pattern, deep breathing practices can take various forms (Brown et al, 2013); during the respiration-force coordinating task, the participants were instructed to keep a constant, slow, and deep diaphragmatic breathing rhythm with a brief pause following the inspiratory/expiratory period of each breathing cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Deep breathing practices, which generally involve inhalation and exhalation of air at a slow rate that is different from regular breath cycles, form an integral component of many meditation programs (Brown and Gerbarg, 2009). A number of studies show that the deep breathing practice may result in marked beneficial effects across a variety of cognitive functions, including inhibitory control, working memory, and attention and emotion regulation (Busch et al, 2012; Brown et al, 2013; Vlemincx et al, 2016; Yadav and Mutha, 2016). Depending on the breathing pattern, deep breathing practices can take various forms (Brown et al, 2013); during the respiration-force coordinating task, the participants were instructed to keep a constant, slow, and deep diaphragmatic breathing rhythm with a brief pause following the inspiratory/expiratory period of each breathing cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Research suggests that practices like pranayama can reduce errors made by children at school [21]. It has been observed that breathing exercises facilitate better retention of recently learned motor skills [22]. Diaphragmatic breathing also improves sustained attention, affect, and cortisol levels [23].…”
Section: Introductionmentioning
confidence: 99%
“…54 ANB is considered slow-paced breathing exercise that can stimulate the vagus nerve to promote neuroplasticity and neurogenesis via release of acetylcholine, epinephrine and brain-derived neurotropic factor (BDNF). 8 Bhavanani et al, suggested that breathing techniques can enhance neuronal information processing to decrease reaction time as the ascending reticular activating system is inhibited.…”
Section: Cellular Mechanismsmentioning
confidence: 99%
“…6,15,16,19,22,30,36 In 14 studies, subjects were asked to hold their breath and/or were given specific duration for inhalation, breath retention and exhalation phase (Table 1 for details) while performing ANB. [7][8][9][10][11][12][13]27,29,31,[37][38][39][40][41] Six studies included the following pattern: breathe out through left nostril, then breathe in through right nostril and repeat this pattern once, twice or three times, before switching the nostrils to breathe out through right nostril, breathe in through left nostril and repeat this once, twice or three times before switching again. 28,[42][43][44]46 Another study involved a mixed pattern of cycles of unilateral nostril breathing, cycles of normal breathing, cycles of opposite unilateral nostril breathing and cycles of alternate nostril breathing.…”
Section: Alternate Nostril Breathing Techniquementioning
confidence: 99%
See 1 more Smart Citation